Third country family members, protagonists of the rd 178/2003. future incidence of the proposal for a directive on free movement of persons - Quirós Fons, Antonio (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
The foreign regulation is not applied to every non-national. EU nationals and their assimilates are excluded. They have a regulation of their own, based on EU citizenship and free movement of persons. There is a beneficiary group whose link is not nationality but family. They are third-country nationals and family members of EU citizens. Only a few of them can be considered in that way within the Spanish and European legislation in force —the recent RD 178/2003—. While this status is not proved, the general regulation derived from the Migration Policy in force, must be applied. Never- theless, the EU legal instruments in preparation impose an enlargement of the relatives admitted.